Mahabbah dan Ma’rifat: Jalan Menuju Tuhan dalam Tasawuf - Besari, Ahiel Ahdi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Sufism is a part of Islamic teachings related to esotericism that emphasizes inner experience and a direct approach to God.love, or divine love, and ma’rifat, or spiritual knowledge of God, are two central concepts in this tradition. The purpose of this article is to examine the relationship betweenlove And ma’rifatas a path to God. To achieve this goal, a literature review was used as a qualitative approach. Contemporary and classical books studied included works by Sufis such as Al-Ghazali, Al-Hujwiri, and Ibn Arabi, as well as the famous female Sufi figure Rābi‘ah Al-‘Adawiyah. Rābi‘ah introduced the concept of pure mahabbah, love for God without any expectation of heaven or fear of hell, as the highest form of spiritual devotion. The results of the study indicate thatlove is the main mover in the spiritual journey, which then leads a Sufi to ma’rifat, which is direct and intuitive knowledge of the Divine reality. These two concepts are not only included in the theoretical framework of Sufism, but also form a transformative foundation for the search for meaning and existential closeness to God amidst the challenges of the modern age.